Pemberdayaan Remaja Putri melalui Edukasi Booklet Konsumsi Tablet Tambah Darah sebagai Upaya Pencegahan Anemia di Posyandu AR-Rahman Sekayu Musi Banyuasin - Devita; Sunartono Sunartono; Eka Vicky Yulivantina (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia remains a prevalent health problem among adolescent girls in Indonesia. Low knowledge and poor adherence to Iron-Folic Acid (IFA) tablet consumption present challenges in anemia prevention efforts. This community service activity aimed to improve adolescent girls’ knowledge and attitudes regarding anemia prevention through education using a booklet. The implementation methods included interactive lectures, group discussions, demonstrations of IFA tablet consumption, and evaluation through pre-test and post-test among 20 adolescent girls aged 15–18 years at Posyandu AR-Rahman Sekayu. The results showed a significant increase in knowledge: the “good” category rose from 25% (pre-test) to 75% (post-test), while the “poor” category decreased from 30% to 0%. A total of 60% of participants reported practicing routine IFA tablet consumption, and 85% stated that the booklet was accessible and easy to understand. Conclusion: Booklet-based education was effective in increasing knowledge and practices of anemia prevention among adolescent girls. This activity has the potential to be scaled up and replicated in other community health posts (posyandu).